Evidence for saddle point-driven charge density wave on the surface of heavily hole-doped iron arsenide superconductors - Quanxin Hu; Yu Zheng; Hanxiang Xu; Junze Deng; Chenhao Liang; Fazhi Yang; Zhijun Wang; Vadim Grinenko; Baiqing Lv; Hong Ding; Chi Ming Yim (Nature Communications)
Abstract Unconventional superconductivity is known for its intertwining with other correlated states, making exploration of the intertwined orders important for understanding its pairing mechanism. In particular, spin and nematic orders are widely observed in iron-based superconductors; however, the presence of charge order is uncommon. Using scanning tunnelling microscopy, and through expanding the phase diagram of iron-arsenide superconductor Ba1−x K x Fe2As2 to the hole-doping regime beyond KFe2As2 by surface doping, we demonstrate the formation of a charge density wave (CDW) on the arsenide surface of heavily hole-doped Ba1−x K x Fe2As2. Its emergence suppresses superconductivity completely, indicating their direct competition. Notably, the CDW emerges when the saddle points approach the Fermi level, where its wavevector matches with those linking the saddle points, suggesting saddle-point nesting as its most probable formation mechanism. Our findings offer insights into superconductivity and intertwined orders, and a platform for studying them in iron-based superconductors close to the half-filled configuration.